PENGARUH APLIKASI PUPUK TRICHO-KOMPOS TERHADAP PERTUMBUHAN SEMAI AREN (Arenga pinnata) PADA MEDIUM GAMBUT - Deden Syatria; M Mardhiansyah; Mukhamadun Mukhamadun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The expansion of the use of peat was not wise, causing the rate of peat destruction to be very fast. Peatlands in Riau have a large enough potential to be planted with various types of forest plants. Efforts are needed to achieve optimal plant growth on peat soils. Trichoderma sp. as Tricho-Compost, it was hoped that it can spur growth and improve the quality of Arenga pinnata plants. The purpose of this study was to determine the effect of Tricho-Compost application on the growth of Arrenga pinnata seedlings on peat media and to determine the best dosage of Tricho-Compost on Arenga pinnata seedling growth on peat media. The research was conducted using a completely randomized design (CRD) consisting of 4 treatments with 5 replications in order to obtain 20 experimental units.The compost of compost at several levels of concentration, namely: D0 = Without Tricho-Compost (Control) application, D1 = 25% Tricho application -Compost + 75% peat soil, D2 = Application 50% Tricho-Compost + 50% peat soil, D3 = Application 75% Tricho-Compost + 25% peat soil. The data obtained from the research results were statistically analyzed using Analysis of Variance (ANOVA) and further analyzed using Duncan's New Multiple Range Test (DNMRT) at the 5% level. The application of Tricho-Compost fertilizer has an effect on the growth of Arrenga pinnata seedlings. The application dose of Tricho-compost D2 fertilizer (application of 50% tricho-compost + 50% peat) shows the best treatment to increase the growth of Arenga pinnata seedlings in peat medium showed of a percent live yield as 96%, height increase as 17.25 cm and a top-root ratio as 3.71.Keywords : Arenga pinnata, Tricho-Kompos, growth